Instantaneous Flood Events Data Analyses in Northern Pakistan - Hussain, Kashif; Shahab, Muhammad (European Scientific Journal, ESJ, 2019)
In large watersheds of Pakistan, a proper flood intensity assessment is a most important concern for many water management applications. The present study investigates the possible best-fit probability distributions technique of uttermost flood events using more than 30 years data (except Mastuj Bridge station) from 15 stream flow stations in northern Pakistan, operated and maintained by Surface Water Hydrology Project (SWHP), WAPDA. Different statistical distribution model, were used to estimate design floods for risk planning and the design of important civil infrastructure. Method of moments was used for estimation of parameters of selective distributions. Four goodness-of-fit statistics test K, A2, χ2 and Root mean square error (RMSE) were applied to evaluate the most appropriate probability distribution. P3, LP3, GEV, and LN were determined best fit distribution model. Among the eight-probability distribution’s P3 fitted 33.3% of the stations, LP3 also fitted 33.3% of the stations, GEV fitted 26.7% of the stations and LN fitted 6.7% of the stations. The more practical result for peak flood were calculated for recurrence intervals of 5-year, 25-year, 50-year, 100-year, 500-year and 1000-years respectively. In future before planning and designing any project such as Hydropower, irrigation systems, Dike, flood disaster assessment and management at Indus and adjacent rivers, P3, LP3, GEV and LN distributions results should be considered more reliable on these locations.